2018
DOI: 10.7752/jpes.2018.02082
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The article provides theoretical background for the stages of professional formation of a physical education teacher determined using fitness technologies. The article contains the analysis of scientific literature and normative documents that regulate professional readiness of a physical education teacher at a higher educational institution for innovative activity. Our work defines the following stages of professional formation of a physical education teacher using fitness technologies: the stage of adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…When performing physical education tests and physical development assessments, a large number of applicants did not have the technical skills and knowledge about the necessity of such evaluations and of the performance of tests. In addition, a scientific analysis of the medical examination of school-age children conducted in Zhytomyr Region during fifteen years showed that the level of sick children ranged from 40.9 to 69.2 % [4,19]. Accordingly, the low indicators of the health status and physical fitness of students are not accidental because university applicants are school graduates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When performing physical education tests and physical development assessments, a large number of applicants did not have the technical skills and knowledge about the necessity of such evaluations and of the performance of tests. In addition, a scientific analysis of the medical examination of school-age children conducted in Zhytomyr Region during fifteen years showed that the level of sick children ranged from 40.9 to 69.2 % [4,19]. Accordingly, the low indicators of the health status and physical fitness of students are not accidental because university applicants are school graduates.…”
Section: Resultsmentioning
confidence: 99%
“…The medical examinations were conducted by doctors at the university's medical center and the municipal polyclinic. The main pedagogical experiment involved 681 students (209 males and 472 females, aged [17][18][19][20][21][22]. The analysis, systematization, and generalization of the literary sources and medical records of students allowed us to form the general situation of the disease incidence of the students of the university and Ukrainian higher educational establishments.…”
Section: Methodsmentioning
confidence: 99%
“…Fitness technologies enable the complex use of modern fitness programs in the process of training classes with students depending on their age characteristics, state of health, level of physical training, forming motivational priorities that promote the development of positive motivation for physical education and independent health activities [7,8,9]. Retrospective analysis of scientific data in pedagogy, theory and methodology of physical education [3,10,11,12] indicates a large amount of theoretical and experimental material for the application of different types and trends of fitness technology in the educational process of physical education. It should be noted that the concepts of fitness technology are constantly changing depending on the development tendencies in the fitness industry [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The scholars [29,30] note that the level of students' health depends significantly on the state of physical education at school, following a healthy lifestyle by school pupils, and the prevention of diseases among pupils, that is, on the initial level of health of a HEI applicant. There has been a significant deterioration of health and a decrease in the level of fitness of young students in Ukraine for many years [31,32]. The examination of the physical development and physical fitness of the students of Polissya National University for thirty years showed that more than 50 % of them could not pass physical tests with "satisfactory results".…”
Section: Introductionmentioning
confidence: 99%